2022
DOI: 10.1097/cad.0000000000001294
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-1α inhibition augments efficacy of programmed cell death 1 antibody in murine prostatic cancer models

Abstract: This study was designed to explore whether hypoxia-inducible factor-1α (HIF-1α) inhibitor could enhance immunotherapy efficacy in prostate cancer. Western blot was used to detect the expression of HIF-1α in the tumor and peritumor tissues from prostate cancer patients. The analysis from Cancer Genome Atlas database was used to show an association between HIF-1α expression and survival rate in prostate cancer patients. Murine prostate cell–derived xenograft (CDX) model was set up in both nude mice and BALB/c mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Hypoxic regulates the expression of HIF-1α, a critical mediator in tumor progression. 25 Stabilization of HIF-1α through extracellular regulated kinase signaling has been linked to the promotion of platinum-resistance in ovarian cancer. 26 The upregulation of HIF-1α has been shown to promote chemotherapy resistance of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic regulates the expression of HIF-1α, a critical mediator in tumor progression. 25 Stabilization of HIF-1α through extracellular regulated kinase signaling has been linked to the promotion of platinum-resistance in ovarian cancer. 26 The upregulation of HIF-1α has been shown to promote chemotherapy resistance of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with PD-1 inhibitors in OS mice model results in a significant reduction in the probability of lung metastasis ( Zheng et al, 2018 ). Although the role of HIF-1α on PD-1/PD-L1 in OS cells remains unconfirmed, inhibiting the expression of HIF-1α can effectively reduce the expression level of PD-1 in glioma and prostate cancer cells ( Ding et al, 2021 ; Shen et al, 2022 ). Decreased expression of HIF-1α and PD-L1 promotes the infiltration of CD8 T cells, and increases the levels of TNF-α, IFN-γ, thereby significantly enhancing the efficacy of anti-PD-1 therapy in gastric cancer cells ( Wang Z. et al, 2023b ).…”
Section: Therapeutic Prospect Of Targeting Hif-1α In the Treatment Of...mentioning
confidence: 99%
“…Inhibition of ENTPD2 by ARL67156 and POM-1 reduces tumor growth and improves the effectiveness of immune checkpoint inhibitors of programmed death-1 (PD-1) (clone RMP1-14) and cytotoxic T-lymphocyte-associated protein-4 (CTLA-4) (clone 9D9), implying that ENTPD2 is a prospective cancer treatment target [ 111 ]. Similarly, the HIF-1α inhibitor IDF-11774 was found to enhance the efficacy of anti-PD-1 treatment in murine prostate cancer xenograft models [ 106 ]. Further analysis revealed that the combination of IDF-11774 with an anti-PD-1 antibody reduced the presence of immunosuppressive cells such as M2 macrophages and myeloid-derived suppressor cells, while increasing the number of effector T cells in the tumor microenvironment [ 106 ].…”
Section: Immunotherapy With Hif Inhibitorsmentioning
confidence: 99%